The effect of different concentrations of chlorine-containing disinfectants on high-frequency contact table in intensive care units: A quasi-experimental study - Li, Jing; Zhang, Yanhua; Zhang, Zhiyun; Zhang, Haixia; Wang, Xiaojuan; Wang, Fuchuan; Wang, Hongyu; Chen, Meiling (PloS one, 2023)
The hospital environment, particularly the intensive care unit (ICU), contributes to the transmission of several nosocomial pathogens, which can survive in this setting for a longer period of time and, in turn, contaminate the surfaces or the medical tools. Thus, appropriate disinfection of these areas and devices are crucial for controlling and preventing further infection. In this study, we examined the effect of different concentrations of chlorine-containing disinfectants (500mg/L, 1000mg/L, and 2000mg/L) on the ICU environment. This quasi-experimental study was based on a convenient sampling method. In this study, High-frequency objects were selected as subjects in ICU, with a total sample of 216.A hall including 6 beds was examined,selecting 4 high-frequency surfaces per bed unit:a bed gear, infusion system, bed end table, and monitor were disinfected with 500, 1000, and 2000 mg/L of chlorine (as Cl2), respectively.The surface dissection was performed at 21:00 o'clock daily, after which ATP fluorescence monitoring and bacterial count detection were performed. There was no significant difference in ATP bioluminescence (F = 2.03, P > 0.05) and bacterial counting (χ2 = 2.03, P > 0.05) when using different concentrations of chlorine-containing disinfectant in the ICU. Yet, compared with high concentration (2000mg/L), a low concentration disinfectant reduced the hospital cost. By reducing the concentration of ICU high-frequency contact table disinfectants, it is possible to reduce the risk of long-term contamination with chlorine-containing disinfectants and reduce the cost of using ICU chlorine-containing disinfectants.